Strategi Bisnis yang Harus Dipahami oleh Pengusaha - Mutiara Sawitri Pane; Zuhrinal M. Nawawi (ManBiz: Journal of Management and Business, 2023)
As an entrepreneur, it is necessary for him to have knowledge related to strategies in running his business. Because by making the right strategy, he will benefit as expected, and vice versa with the wrong strategy will cause losses for business owners and even allow entrepreneurs to go bankrupt. Of course, every entrepreneur does not want to experience bankruptcy or big losses. For this reason, it is necessary for entrepreneurs to understand strategies in doing business as a way to achieve success. This study will explain the various strategies that entrepreneurs need to know in running their business. The method used in explaining the entrepreneur's strategy is descriptive qualitative in which the researcher will conduct a literature study to produce various references related to the strategies that entrepreneurs can go through to run their business. This research explains that there are many strategies that entrepreneurs can go through, including through digital, considering that today is thick with the digital world, so as an entrepreneur he will continue to run a business that can be reached by the younger generation because their world is generally through digital as a means of communication. Keywords: entrepreneur, business, digital, strategy